Episodic Future Thinking about the Ideal Self Induces Lower Discounting, Leading to a Decreased Tendency toward Cheating - Wu, Wen-Hsiung; Cheng, Wen; Chiou, Wen-Bin (Frontiers in Psychology, 2017)
Delay discounting refers to a pervasive tendency toward preferring smaller immediate gains over larger future gains. Recent empirical research has shown that episodic future thinking (EFT; i.e., projecting oneself into the future to pre-experience forthcoming events) can reduce the tendency toward discounting. A common tenet of psychological theories of crime is that delinquency results from focusing on short-term gains while failing to consider adequately the longer-term consequences of delinquent behavior. We investigated whether an EFT intervention involving the ideal self could induce lower discounting rates and, as a consequence, reduced delinquency. The results showed that, compared with control participants, participants engaging in EFT, that is, envisaging life events that would be experienced by their ideal selves, exhibited a lower discounting rate in a monetary choice task (Experiments 1 and 2), as well as a decreased tendency to make delinquent choices in imaginary scenarios (Experiment 1) and cheat in a matrix task (Experiment 2). The discounting tendency mediated the relationship between engaging in EFT pertaining to the ideal self and the tendency toward morally questionable behavior (Experiments 1 and 2). The findings of the two experiments indicate that engagement in EFT with a focus on the ideal self is sufficient to induce lower discounting rates, by promoting consideration of distant costs and thus increasing resistance to delinquent involvement and cheating (given the temptation of the immediate benefits that may accrue from such behavior). The current research constitutes an innovative approach to delinquency prevention and the promotion of morality.